Pola Peresepan Antibiotik pada Pasien Komplikasi Diabetes Melitus di RSUD Panembahan Senopati Bantul - Eva Nurjanah; Daru Estiningsih; Nurul Kusumawardani; Ninisita Sri Hadi (Fakultas Farmasi Universitas Pancasila, 2023)
Diabetes Mellitus, one of the non-communicable diseases (NCDs), is the leading cause of death in addition to cardiovascular disease, cancer, and chronic respiratory disease. The Basic Health Research (Riskesdas) recorded that Yogyakarta experienced a prevalence increase of 97% in 2013-2018, the second-highest in Indonesia. Uncontrolled sugar levels cause deterioration of the immune system. This study aims to determine the pattern of prescribing antibiotics and the occurrence of comorbid complications, both infectious and non-infectious. This was a non-experimental descriptive study with a cross-sectional design. The data was collected from patient's medical records retrospectively from July to December 2019. Furthermore, 65 medical records were taken using a simple random sampling method. A descriptive statistical analysis was performed, and the results were presented as percentages. The percentage of infectious and non-infectious comorbid diabetes mellitus II in Panembahan Senopati Bantul Hospital was 22.2% and 77.8%, respectively. The prescribing pattern primarily used was ceftriaxone (23.5%). The antibiotic class mainly prescribed was cephalosporin (49%).